Security, Privacy, and Applied Cryptography Engineering 6th International Conference, SPACE 2016, Hyderabad, India, December 14-18, 2016, Proceedings - Carlet, Claude; Hasan, M. Anwar; Saraswat, Vishal (Security and Cryptology, 2016)
This book constitutes the refereed proceedings of the 6th International Conference on Security, Privacy, and Applied Cryptography Engineering, SPACE 2016, held in Hyderabad, India, in December 2016. This annual event is devoted to various aspects of security, privacy, applied cryptography, and cryptographic engineering. This is indeed a very challenging field, requiring the expertise from diverse domains, ranging from mathematics to solid-state circuit design.